A New Nomogram to Predict the Success of Shock Wave Lithotripsy in Ureteral Stones - Muhammed Fatih Simsekoglu; Engin Derekoylu; Mustafa Ozkaya; Muhammet Demirbilek; Ugur Aferin; Berin Selcuk; Ahmet Erozenci; Bulent Onal (International Journal of Clinical Practice)
Purpose. To design a new nomogram predicting the probability of stone-free status of shock wave lithotripsy (SWL) in patients with ureteral stones. Materials and Methods. We retrospectively enrolled 2,144 patients with ureteral stones who underwent SWL between January 1993 and April 2020. The demographic and clinical parameters were assessed. The predictors of stone-free status following SWL were identified. A logistic regression-based nomogram was created by including the significant predictors in the multivariate analysis. Results. The mean age was 42.93 ± 13.85 in the stone-free group (Group 1) and 46.51 ± 13.66 in the treatment-failure group (Group 2) (p=0.001). The cutoff value of the age was 45.5 years. The mean stone load was 0.71 ± 0.36 cm2 in Group 1 and 0.96 ± 0.51 cm2 in Group 2 (p=0.001). Of the 2,144 patients, 1,708 (79.6%) were stone-free within the first three SWL sessions. According to the multiple logistic regression analysis, older age, a stone load larger than 1 cm2, the presence of multiple stones, third-generation lithotripter use, and pre-SWL catheterization were statistically associated with low stone-free rates. The C-index was determined to be 0.75 in the bootstrapping method. Conclusion. A stone load larger than 1 cm2, age older than 45.5 years, the presence of multiple stones, new- (third-) generation lithotripter use, and pre-SWL catheterization had statistically significant effects on lower stone-free rates in patients who underwent SWL due to ureteral stones. A nomogram was developed to predict the success of SWL. As a result of the internal validation of the nomogram, it was concluded to be suitable for clinical use.